Effect of microstructure on the mechanical properties of lithium disilicate glass-ceramics. (June 2018) - Hallmann, Lubica; Ulmer, Peter; Kern, Matthias
Abstract: The mechanical properties of lithium disilicate glass-ceramics depend on various factors, a prominent one being their microstructure. The aim of this review article is to elucidate the effect of processing parameters such as annealing temperature, holding time, number of heating stages and chemical composition and additives on the microstructure and physical properties of these glass-ceramics.